Excavation Face Stability Analysis of EPB Shield in Half-Chamber Tunneling Mode - ZHENG Weigang; ZHANG Tao; WU Xinglin; LI Hailong; ZHANG Hongzhi; CHEN Peng; SHU Jicheng (Chengshi guidao jiaotong yanjiu)
［Objective］ In complex geological environments such as soft upper and hard lower or weathered rock layers, during the construction of EPB (earth pressure balance) full chamber tunneling mode, the slag liquid level is too high, the cutterhead generates excessive torque, causing lots of energy consumption in shield tunneling. Therefore, the half-chamber tunneling mode is often used in practice to reduce the slag liquid level in the excavation chamber. However, excessively low liquid levels will increase the risk of excavation face instability. Thus, it is necessary to study the excavation face stability issue of EPB shield in half-chamber tunneling mode. ［Method］ Based on the upper limit theorem of the limit analysis method, a 3D logarithmic spiral failure model considering half-chamber support mode is proposed. The influence of support pressure distribution form and in-chamber muck height on the stability of EPB shield tunnel excavation face is studied. Combined with numerical simulation and instability model, the reasonable height of muck in chamber is explored, and the limit support pressure under various support modes is compared. Factors such as cover soil thickness, cohesion, internal friction angle that influence the limit support pressure are discussed. ［Result & Conclusion］ The stability of the excavation face can be significantly improved by increasing the supporting medium density, while increasing the tunnel diameter is not conducive to the stability of the excavation face. The soil chamber supporting pressure gradient, the height of in-chamber muck and cohesion are all negatively correlated with the limit support pressure.